Effect of Work Environment, Motivation and Job Satisfaction on Employee Performance at PT. Dua Tiga Sejahtera - Asraf, Asraf; Nabila, Maya; Bagea, Arfin; Sahili, Laode; Abbas, Bakhtiar (PT. Riset Press International, 2023)
This study aims to determine and analyze the influence of the work environment, motivation and job satisfaction on the performance of employees of PT. Dua Tiga Sejahtera. The object of this research is the work environment, motivation and job satisfaction on the performance of employees of PT. Dua Tiga Sejahtera. The population in this study are all employees at PT. Dua Tiga Sejahtera as many as 33 employees. While the sample in this study were all employees, namely 33 respondents. The analytical tool used is multiple linear regression using SPSS 25 software. Based on the results of the research conducted, it can be concluded that (1) work environment, motivation and job satisfaction have a positive and significant effect on employee performance; (2) the work environment has a positive and significant effect on employee performance; (3) Motivation has a significant effect on employee performance; (4) job satisfaction has a positive and significant effect on employee performance.